(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Critical thinking is a main skill that enables students to analyze data, solve issues, and make informed decisions. This article explores the importance of increasing critical thinking skills in students and shows effective strategies for encouraging these skills in educational sunsets. It debates the role of inquiry-based learning, problem-solving activities, and open-ended arguments in enhancing students’ mental abilities. The study also emphasizes the difficulties teachers’ face ancouraging critical thinking and proposes practical solutions. Advancing critical thinking skills makes students for academic success and provides them with crucial life skills for future challenges.